A Chiral Lanthanide Tag for Stable and Rigid Attachment to Single Cysteine Residues in Proteins for NMR, EPR and Time‐Resolved Luminescence Studies. Issue 51 (29th July 2021) - Herath, Iresha D.; Breen, Colum; Hewitt, Sarah H.; Berki, Thomas R.; Kassir, Ahmad F.; Dodson, Charlotte; Judd, Martyna; Jabar, Shereen; Cox, Nicholas; Otting, Gottfried; Butler, Stephen J.
Abstract: A lanthanide‐binding tag site‐specifically attached to a protein presents a tool to probe the protein by multiple spectroscopic techniques, including nuclear magnetic resonance, electron paramagnetic resonance and time‐resolved luminescence spectroscopy. Here a new stable chiral Ln III tag, referred to as C12, is presented for spontaneous and quantitative reaction with a cysteine residue to generate a stable thioether bond. The synthetic protocol of the tag is relatively straightforward, and the tag is stable for storage and shipping. It displays greatly enhanced reactivity towards selenocysteine, opening a route towards selective tagging of selenocysteine in proteins containing cysteine residues. Loaded with Tb III or Tm III ions, the C12 tag readily generates pseudocontact shifts (PCS) in protein NMR spectra. It produces a relatively rigid tether between lanthanide and protein, which is beneficial for interpretation of the PCSs by single magnetic susceptibility anisotropy tensors, and it is suitable for measuring distance distributions in double electron–electron resonance experiments. Upon reaction with cysteine or other thiol compounds, the Tb III complex exhibits a 100‐fold enhancement in luminescence quantum yield, affording a highly sensitive turn‐on luminescence probe for time‐resolved FRET assays and enzyme reaction monitoring. Abstract : Lanthanoid keys to proteins : A stable chiral lanthanide(III) tag reacts spontaneously and quantitatively with a cysteine residue to generate a stable thioether bond. The lanthanide‐binding tag presents a tool to probe proteins using multiple spectroscopic techniques, including NMR, electron paramagnetic resonance and time‐resolved FRET experiments.